2015
DOI: 10.4238/2015.january.23.16
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3-base pair deletion of the CRYAA gene identified in a large Chinese pedigree featuring autosomal dominant congenital perinuclear cataract

Abstract: ABSTRACT. Congenital cataract is caused by reduced transparency of the lens resulting from metabolic disorders during the fetal period. The disease shows great heterogeneity both clinically and genetically. We identified a 4-generation ethnic Han Chinese family affected by autosomal dominant congenital perinuclear cataract. The patients underwent full clinical and ophthalmologic examinations to rule out any concomitant disorders. Blood samples were collected and genomic Novel CRYAA mutation underlying congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Crystallins are the predominant lens structural proteins of mammals and have a significant function in providing transparency and light transmission to the eye lens 32 . However, mutations in the genes encoding crystallin proteins lead to abnormal expression, which might disrupt lens opacity and even cause blindness 12 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Crystallins are the predominant lens structural proteins of mammals and have a significant function in providing transparency and light transmission to the eye lens 32 . However, mutations in the genes encoding crystallin proteins lead to abnormal expression, which might disrupt lens opacity and even cause blindness 12 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…[13,2022] For example, c.246_248delCGC (p.117delR), a novel mutation of the CRYAA gene, has been detected in a Chinese family with perinuclear congenital cataracts of autosomal type. [15] Su et al [23] also identified a disease-causing mutation in the CRYAA gene, c.161G > C (p.R54P), with autosomal dominant Y-suture cataracts. Jiaox et al [4] have reported 2 novel missense mutations, namely p.R11C and p. R12C of the CRYAB gene, show relations with autosomal recessive congenital nuclear cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The CRYAA gene is mapped to chromosome 21q22.3, which consists of 3 exons. [15] Located on chromosome 11q23, CRYAB encodes for a member of the sHSP family composing of 175 amino acid protein, [4] and functions as a molecular chaperone, restraining the accumulation of denatured proteins after exposure to stresses, including radiation, heat shock, and oxidative stress. [13] Currently, over 40 loci have been mapped in congenital cataract development.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one severe consequence of mutants in the genetic information. Besides widely researched single nucleotide polymorphism, genetic deletion also associated with several diseases, such as a 3‐base pair deletion of CRYAA gene lead to an autosomal dominant congenital perinuclear cataract in large Chinese pedigree . In addition to several bases deletion, exons deletion is also common in genetic mutants.…”
Section: Introductionmentioning
confidence: 99%